Methods of Formation of Legal and Educational Competence of Future Teachers - Begmatov Raximjon Raxmonqulovich (Genius Publishing Group, 2022)
The stages of self-improvement, forms of self-assessment through self-development, analysis and monitoring in improving the professional competence of the future specialist are given
Keywords: Concept; pedagogy; competence; legal and educational